The critical role of job embeddedness: The impact of psychological empowerment and learning orientation on organizational commitment - Yoon, Dong-Yeol; Han, Caleb Seung-Hyun; Lee, Soo-Kyoung; Cho, Jun; Sung, Moonju; Han, Soo Jeoung (Frontiers in Psychology, 2022)
Job embeddedness (JE) has been recognized as a key factor to address the issue of employee turnover and employee attitudes. This study explores underlying mechanisms of job embeddedness that link the organizational environment and the individuals’ perceptions of the job. Particularly, the effects of psychological empowerment and learning orientation on organizational commitment were examined. This study hypothesizes that psychological empowerment (PE) and learning orientation (LO) should influence organizational commitment (OC) and job embeddedness plays a significant mediating role in these relationships. Data were collected from 27 offices of Human Resource Development Service of Korea (governmental agency) located in major cities in South Korea. Results indicate that all hypothesized relationships (PE and JE, LO and JE, LO and OC, JE and OC, and the mediating role of JE) are supported, except for psychological empowerment and organizational commitment. While the impact of psychological empowerment was not significantly related to organizational commitment, it is notable that through job embeddedness, psychological empowerment had indirect effects on organizational commitment. Further, learning orientation had significant effects on job embeddedness and organizational commitment. Lastly, the most compelling finding is a full mediation of job embeddedness in the relationship between psychological empowerment and organization commitment. Implications for research and practice are discussed.